2021
DOI: 10.1002/pa.2654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trade openness, human capital, and institutional performance on economic growth: Evidence from Organization of Islamic Cooperation countries

Abstract: The study analyzes the impact of trade openness, human capital, and institutional performance on economic growth in OIC countries. The traditional methodologies of panel data ignore the issues of cross-sectional dependence (CD) and heterogeneity and give spurious results. A novel econometric technique "dynamic common correlated effects (DCCE)" is used to tackle these issues. The long-run estimates indicate that trade openness, human capital, and public expenditure have a positive and significant association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 85 publications
5
15
0
Order By: Relevance
“…The coefficient of institutional quality (INS) had a significant and positive impact on the distribution of economic growth except for quantiles 0.25 and 0.50, in which case it was insignificant. The finding is consistent with the finding of Hasan et al (2009), Ahmad and Hall (2017) and Ali et al (2021). However, the result of GMM estimations illustrated that good institutional quality had a detrimental effect on economic performance.…”
Section: Empirical Findingssupporting
confidence: 93%
“…The coefficient of institutional quality (INS) had a significant and positive impact on the distribution of economic growth except for quantiles 0.25 and 0.50, in which case it was insignificant. The finding is consistent with the finding of Hasan et al (2009), Ahmad and Hall (2017) and Ali et al (2021). However, the result of GMM estimations illustrated that good institutional quality had a detrimental effect on economic performance.…”
Section: Empirical Findingssupporting
confidence: 93%
“…and more efficient management contribute to higher performance. This is supported by the previous studies (Ali et al, 2021;Bui and Bui, 2020;Chiang and Ab-Rahim, 2016;G€ achter and Gkrintzalis, 2017;Le et al, 2016), which reported that higher capital of banks results in higher profitability level. Finally, LLPTA showed a negative and statistically significant relationship with banks' performance in each model, indicating that banks' performance is lessened by the higher credit risk of each bank (Omoke and Opuala-Charles, 2021;Raji et al, 2017;Shaohua et al, 2021;Soedarmono and Tarazi, 2016;Tahir et al, 2019;Triki et al, 2017;Xu, 2016).…”
Section: Trade Opennesssupporting
confidence: 85%
“…Higher values of these proxies indicate a higher cost of financial intermediation and vice versa. Following Ali et al (2021) and Sharma and Anand (2018), the bank performance was proxied by an alternative measure: the ratio of annual values of return on assets before loan loss provisions and taxes over average total assets (ROA). The higher value of this measure means higher performance and vice versa.…”
Section: Rule Of Law Rolmentioning
confidence: 99%
See 2 more Smart Citations